Idiopathic Hypercalciuria and Hyperparathyroidism - Adams, Peter (1970)
With provocative tests of parathyroid activity based on phosphate deprivation and the administration of chlorothiazide 8 out of 19 patients with idiopathic hypercalciuria developed hypercalcaemia. Five of the eight underwent exploration of the neck and four of them had parathyroid adenomas; the fifth patient had “normal” glands but responded satisfactorily to subtotal parathyroidectomy. One patient who failed to develop hypercalcaemia had primary chief cell hyperplasia of the parathyroids.